Efektivitas Penegakan Hukum Persaingan dalam Kelangkaan BBM: Peran KPPU dan Regulasi Impor Satu Pintu - Kurnia, Galih Pradana; Meizaroh; Febrianto, Mochamad Akbar; Marasabessy, Rizqy Maulana (Institut Agama Islam Negeri (IAIN) Bone, 2025)
The limited supply of Fuel Oil (BBM) often has wide-ranging effects on the economy, including transportation, production costs, and price stability. To ensure fuel availability, the government implemented a single-window import policy as stipulated in the Ministry of Energy and Mineral Resources Circular Letter No. T-19/MG.05/WM.M/2025. However, this policy has the potential to create monopolistic practices, as imports must be conducted through PT Pertamina as the sole distributor. This study aims to analyze the effectiveness of competition law enforcement in the context of BBM scarcity, focusing on the role of the Business Competition Supervisory Commission (KPPU) and the single-window import policy. The research employs a normative juridical method using a statutory and conceptual approach, analyzing relevant legal frameworks, the theory of legal effectiveness, and the principles of fair business competition. The results show that while the single-window import policy enhances distribution efficiency and government oversight, it also risks reinforcing Pertamina’s dominance and limiting private sector participation. In conclusion, stronger coordination between KPPU and policymakers is required to ensure that BBM import regulations align with fair competition principles while maintaining national energy security in an equitable and sustainable manner.